Cadaveric Study of Anatomic Far Distal Musculocutaneous and Median Nerve Communication - Hussain, Namath S (Cureus, 2016)
One of the more commonly reported variations in musculocutaneous and median nerves is a communication between the two. Such communications have been noted in the literature for well over a century, and numerous studies have attempted to quantify their rate of incidence and classify their different patterns. Most communications occur close to the brachial plexus in the proximal arm; communications distal to the musculocutaneous nerve perforation of the coracobrachialis have been reported with less frequency, and several rare and unique communication patterns have been reported as case studies. This paper describes a case of a communicating branch between the musculocutaneous and median nerves, distal to the origin of the brachialis muscle. This communication was found during a routine educational dissection and is closer to the level of the elbow than previously documented communications that are distal to the musculocutaneous perforation of the coracobrachialis. Identification and documentation of the variety of musculocutaneous and median nerve communications is relevant to clinical diagnosis of peripheral nerve pathologies, as well as for planning surgical approaches and procedures.